In vivo assessment of DNA damage and protective effects of extracts from Miconia species using the comet assay and micronucleus test - Serpeloni, Juliana Mara; dos Reis, Mariana Bisarro; Rodrigues, Juliana [UNESP]; dos Santos, Lourdes Campaner [UNESP]; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP]; Dokkedal, Anne L. [UNESP]; Colus, Ilce Mara S. (Oxford University Press, 2008)
The genus Miconia comprises similar to 1000 species belonging to the Melastomataceae family. Several crude plant extracts from Miconia and their isolated compounds have shown biological activities, such as analgesic and anti-neoplastic action; however, no studies concerning their effects on DNA are available. The present study aimed to evaluate, in vivo, the genotoxic and mutagenic effects of four species of plants from Miconia genus using the comet assay and micronucleus test. Their possible protective effects were also evaluated in experiments associating the plant extracts with cyclophosphamide (CPA). The methanolic extracts of Miconia albicans, Miconia cabucu, Miconia rubiginosa, Miconia stenostachya and the chloroformic extract of M. albicans were investigated. For genotoxic and mutagenic evaluations, three concentrations were tested, 200, 400 and 540 mg/kg body weight (bw), based on the solubility limit of the extract in distilled water. For the protective effects, only the highest dose was evaluated against 40 mg/kg bw of CPA. Blood was removed from mice tails pre- (T0) and post-treatment (T1-30 h) for the micronucleus test and 24 h post-treatment for the comet assay. The Student's t-test was used to compare data obtained at T0 and T1, the analysis of variance-Tukey test was used to compare between groups in the micronucleus test and the Kruskal-Wallis and Dunn's test were used to compare different groups in the comet assay. All the extracts induced alterations in DNA migration (comet assay); however, no mutagenic effect was observed in the micronucleus assay. All extracts showed a protective effect against CPA in both assays. Our study showed that the use of crude extracts could be more advantageous than the use of isolated compounds. The interaction between phytochemicals in the extracts showed efficacy in reducing mutagenicity and improving the protective effects.